2011
DOI: 10.1002/chin.201113005
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Crystal Chemistry and Stability of “Li7La3Zr2O12” Garnet: A Fast Lithium‐Ion Conductor.

Abstract: Garnet: A Fast Lithium-IonConductor. -Single crystals of the title compound are prepared by sintering mixtures of ZrO2, La2O3, and Li2CO3 using ceramic crucibles in initial steps and later sealed Pt capsules. The samples contain small amounts of Al, probably originating from the crucibles. Li7La3Zr2O12 crystallizes in the cubic space group Ia3d with Z = 8 (single crystal XRD) between 100 and 500 K. Li atoms are located on at least two structural sites that are partially occupied, while other Li atoms in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
139
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(157 citation statements)
references
References 1 publication
14
139
3
1
Order By: Relevance
“…showed that LLZO is crystallized with both cubic and tetragonal symmetry, with the cubic phase exhibiting a lithium-ion conductivity two orders of magnitude higher than that for the tetragonal phase 12 Li sites are partially occupied in the LLZO structure. Ta 5+ 14 , Nb 5+ 15 , Te 6+ 16 , and W 6+ 17 that substitute on the Zr 4+ site, as well as Al 3+ 11 and Ga 3+ 18-26 that substitute in the Li sublattice, have been employed to stabilize the cubic phase.…”
Section: Introductionmentioning
confidence: 99%
“…showed that LLZO is crystallized with both cubic and tetragonal symmetry, with the cubic phase exhibiting a lithium-ion conductivity two orders of magnitude higher than that for the tetragonal phase 12 Li sites are partially occupied in the LLZO structure. Ta 5+ 14 , Nb 5+ 15 , Te 6+ 16 , and W 6+ 17 that substitute on the Zr 4+ site, as well as Al 3+ 11 and Ga 3+ 18-26 that substitute in the Li sublattice, have been employed to stabilize the cubic phase.…”
Section: Introductionmentioning
confidence: 99%
“…7. In the literature [1,14,15], the two peaks at ~70 ppm and ~82 ppm are attributed to Al 3+ located in the 24d sites and 48g/96h sites in the garnet phase respectively, 48g and 96h being unresolved as they are neighbor sites (see Fig. 1) [10].…”
Section: Microscopic LI Dynamicsmentioning
confidence: 96%
“…1) [1,6]. Due to partial occupancy of identified Li sites, the diffusion of Li + occurs by a concerted migration mechanism [4,7,8], and the Li content and its distribution among 24d and 48g/96h sites affects the activation energy of the diffusion process [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geiger et al [8] are one of the first groups to note the contamination by Al from the crucible during sintering process and its influence on the stabilizing of the cubic garnet phase. Alternatively, other researches have revealed that the Al acts as a sintering additive by residing in the grain boundaries and also inside of the grain creating more Li-ion vacancies improving the Li-ion conductivity [9][10][11].…”
mentioning
confidence: 99%